WORKSHOP PENINGKATAN KOMPETENSI PENANGANAN PELANGGARAN DAN PENGKAJIAN HUKUM UNTUK PANWASLU KECAMATAN SE- KABUPATEN MUARO JAMBI - Pebrianto, Dony Yusra; Putra, Akbar Kurnia; Ardianto, Budi; Munandar, Tri Imam (Penerbit Widina, Widina Media Utama, 2024)
The upcoming 2024 General Election (Pemilu) is a new milestone in the conduct of democratic festivities in Indonesia. The year 2024 marks the starting point where elections are held simultaneously every five years, considering another dimension, which is the simultaneous holding of Regional Head Elections (Pilkada) in the same year. One of the cornerstones of the Election Supervisory Board (Bawaslu) is the Sub-district Election Supervisory Committee, known as Panwascam. Panwascam is the lowest-level election supervisory institution that is most effective and equipped to handle electoral violations while serving as a filter for handling violations. Therefore, the capacity and competence of Panwascam are crucial in handling electoral violations. The Chairperson and Members of Bawaslu Muaro Jambi during the 2020 Pilkada had to deal with cases of alleged ethical violations (even if found not proven to have violated ethics). However, what is of concern is that these reports emerged as a consequence of the handling of violations carried out by Bawaslu Muaro Jambi Regency. This workshop will enhance the understanding and knowledge of Panwascam, who predominantly do not have a legal education background, to comprehend the concepts of reasoning, interpretation, and legal analysis. ABSTRAKPemilihan Umum (Pemilu) serentak 2024 mendatang merupakan warna baru dalam penyelenggaraan pesta demokrasi di Indonesia. Tahun 2024 merupakan starting point dimana Pemilu diselenggarakan secara serentak setiap lima tahun sekali mengingat dimensi lain yakni Pemilihan Kepala Daerah (Pilkada) juga dilaksanakan secara serentak di tahun yang sama. Salah satu ujung tombak Bawaslu adalah Pengawas Pemilu Kecamatan atau yang dikenal dengan sebutan Panwascam. Panwascam merupakan Lembaga pengawas pemilu terbawah yang paling efektif dan memiliki kelengkapan organ penanganan pelanggaran Pemilu sekaligus sebagai filter penanganan pelanggaran. Maka dalam hal ini tentu kepasitas dan kompetensi Panwascam sendiri dituntut dalam hal penanganan pelanggaran Pemilu. Ketua dan Anggota Bawaslu Muaro Jambi pada Pilkada 2020 harus berhadapan dengan perkara dugaan pelanggaran etik (sekalipun diputuskan tidak terbukti melanggar etik), namun yang menjadi perhatian adalah laporan ini muncul karena imbas dari penyelesaian penanganan pelanggaran yang dilakukan oleh Bawaslu Kabupaten Muaro Jambi. Dengan dilakukannya Workshop ini akan dilakukan peningkatan pemahaman dan pengetahuan Panwascam yang dominan bukan berlatar belakang Pendidikan hukum untuk dapat memahami Konsep penalaran dan penafsiran serta pengkajian hukum.